2013
DOI: 10.3350/cmh.2013.19.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Current consensus and guidelines of contrast enhanced ultrasound for the characterization of focal liver lesions

Abstract: The application of ultrasound contrast agents (UCAs) is considered essential when evaluating focal liver lesions (FLLs) using ultrasonography (US). Microbubble UCAs are easy to use and robust; their use poses no risk of nephrotoxicity and requires no ionizing radiation. The unique features of contrast enhanced US (CEUS) are not only noninvasiveness but also real-time assessing of liver perfusion throughout the vascular phases. The later feature has led to dramatic improvement in the diagnostic accuracy of US f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(107 citation statements)
references
References 92 publications
(101 reference statements)
1
106
0
Order By: Relevance
“…As for the inter-observer agreement, the radiologists were fairly consistent in their assessment, but no effect of contrast injection was found. It is often asserted that standardized and adequate training is needed to obtain optimal and reproducible results from ultrasound examinations, including CEUS [4]. For a complete examination, it is important with a detailed written protocol to establish the exact images that constitute a comprehensive examination [15].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As for the inter-observer agreement, the radiologists were fairly consistent in their assessment, but no effect of contrast injection was found. It is often asserted that standardized and adequate training is needed to obtain optimal and reproducible results from ultrasound examinations, including CEUS [4]. For a complete examination, it is important with a detailed written protocol to establish the exact images that constitute a comprehensive examination [15].…”
Section: Resultsmentioning
confidence: 99%
“…Contrast-enhanced ultrasonography (CEUS) has improved both the detection and characterization of focal liver lesions and is a useful imaging method for distinguishing benign from malignant liver lesions [2,3]. There are three vascular phases, the late phase being the most important phase for distinguishing benign from malignant lesions, the hypovascularisation in this phase being the most specific signs of malignancy [4,5]. Previous studies have shown that CEUS is an accurate imaging method for the characterization of focal liver lesions and could be compared with contrast-CT and contrast MRI [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both readers were blinded to clinical features, laboratory examinations and other imaging findings. Then readers were asked to provide the most likely diagnosis (i.e., benign or malignant diagnosis, pathological diagnosis or indeterminate) for each focal liver lesion according to standard diagnostic criteria [3,4].…”
Section: Imaging Analysismentioning
confidence: 99%
“…4 Taye et al, on comparing the results obtained with a golden standard (HIV test algorithm), reported a sensitivity and specificity of urine EIA test kit as 99.5% and 98.3%, respectively, thus, once again highlighting, the utility of urine test as an alternative method for HIV antibody detection, with greater patient acceptance to give urine samples than serum or whole blood test. In India, Nag et al demonstrated in 65 individuals with unknown HIV status that the urine EIA test was 100% sensitivity and 88.8 % specificity.…”
mentioning
confidence: 99%